Sensitivity analysis of factors affecting the stability of high fill slopes - XIAOBING, Cheng; DZHEDZHULA, Viacheslav (Ways to Improve Construction Efficiency, 2025)
In this study, a systematic analysis of the stability of unsupported tertiary high-fill slopes was carried out using the FLAC3D numerical simulation method, focusing on the nonlinear effects of fill parameters, contact boundary conditions and geometry on the coefficient of safety. The results showed that: Both the fill cohesion and the angle of internal friction showed a marginal decreasing effect on the factor of safety (the growth rate of the factor of safety decreased from 108% to 5.8% when the cohesion was increased from 0 kPa to 40 kPa, and the enhancement efficiency was significantly attenuated after the angle of internal friction exceeded 30°); The contact boundary step height change triggered the slip surface migration mechanism, 1.5m step height formed a localized safety factor recovery anomaly due to the slip surface cutting into the pebble layer, and 3m step width reduced the contact surface shear stress concentration by 65% through stress diffusion; The decrease in the safety factor accelerates when the slope gradient exceeded 45°, and the increase in the width of the unloading platform to 5 m increased the safety factor beyond the critical value of 1.0 by 30.5%. The FLAC3D numerical model realized the visualization prediction of sliding surface migration and stress redistribution, and the critical threshold effect it reveals provided theoretical support for the dynamic construction regulation. The study revealed the threshold effect for the conversion of damage modes of fill slopes, established a stability optimization framework considering the synergistic effect of parameters, and provided a theoretical basis for the design of high-fill slopes based on the regulation of strength parameters, optimization of interface geometry, and platform width proportioning.